UNCROWNED NOVEL DIPTYCH BY DITA TÁBORSKÁ - Gilk, Erik (Bohemica Olomucensia, 2020)
The paper deals with two novels written by Dita Táborská (*1981), a newcomer in contemporary Czech literature. Her literary works Malinka (2017) and Běsa (2018) are connected with the same topic and some of the figures. We can determine her proses as psychological and social novels with the dominant topic of interpersonal relations, especially among parents and their children (also adoptive ones). The author of the paper analyses especially narrative methods and construction of the main figures in Táborská's novels and also summarizes their critical reception.
Keywords: Czech literature after 1989; Czech fiction; adoption; Dita Táborská